THE CONCEPT OF NORM IN PROFESSIONAL (LEGAL) TRANSLATION AND INTERPRETING: THE TRAINEE (USER) VIEW - KOŚCIAŁKOWSKA-OKOŃSKA, Ewa (Comparative Legilinguistics, 2017)
The concept of translation norm has occupied a prominent place in Translation Studies as a terminological challenge for scholars and the reflection of their research fields. The emergence and internalisation of norms is a natural consequence of the socialisation process since norms can be also used as evaluation criteria for certain social (permissible and acceptable) behaviours. However, the operation of norms in translation is hard to be observed: the objects of direct observation are products of the translation process and results of norm-governed translator behaviour. A question might be asked whether norms hinder or rather facilitate the process – a potential answer suggests the dependence of norm application on the translator’s experience and knowledge accrued as factors central for successful performance. These factors are manifested in the performance of professional translators and interpreters, therefore the article focuses initially on the concept of professionalism in translation and interpreting. This is followed by a brief introduction of the notion of norms positioned in the context of translating and interpreting legal texts. The article closes with the presentation of the survey conducted among translation and interpreting trainees.